Supernumerary Teeth in Primary Dentition and Early Intervention: A Series of Case Reports - Rakesh N. Bahadure; Nilima Thosar; Eesha S. Jain; Vidhi Kharabe; Rahul Gaikwad (Case Reports in Dentistry)
Supernumerary teeth are considered as one of the most significant dental anomalies during the primary and early mixed dentition stages. They are of great concern to the dentists and parents because of the eruption, occlusal, and esthetic problems they can cause. Supernumerary teeth occur more frequently in the permanent dentition but rarely in primary dentition. Mesiodens is the most common type of supernumerary teeth but rarely seen in lower arch. Early recognition and diagnosis of supernumerary teeth is important to prevent further complications in permanent dentition. Four cases of supernumerary teeth with mesiodens in upper and lower arch in primary dentition and their management have been discussed.